2017
DOI: 10.1007/s00415-017-8659-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum neuron specific enolase may be a marker to predict the severity and outcome of cerebral venous thrombosis

Abstract: The objective is to explore the effective of baseline serum neuron specific enolase (NSE) on predicting the severity and outcome in patients with cerebral venous thrombosis (CVT). A total of 156 patients confirmed as CVT in Xuanwu Hospital were enrolled in this retrospective study from March 2011 through September 2016. The severity was evaluated with the National Institutes of Health Stroke Score (NIHSS), intracranial pressure (ICP), and CVT-related complications; the outcome was evaluated by modified Rankin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 25 publications
3
24
0
Order By: Relevance
“…[38,39] We obtained a positive correlation between the presence of NSE and a worse neurological status on the first day, and between S100B and a poor status on the first and 30th day of stroke, which is consistent with the observations reported by other authors. [15,[40][41][42] We observed a positive correlation between the concentrations of NSE and S100B.…”
Section: Discussionsupporting
confidence: 49%
“…[38,39] We obtained a positive correlation between the presence of NSE and a worse neurological status on the first day, and between S100B and a poor status on the first and 30th day of stroke, which is consistent with the observations reported by other authors. [15,[40][41][42] We observed a positive correlation between the concentrations of NSE and S100B.…”
Section: Discussionsupporting
confidence: 49%
“…14 NSE could be a reliable marker of neuronal injury and show neuroprotection role as it controls neuronal survival and differentiation. 16 Several studies have suggested that unconjugated bilirubin was neurotoxic to astrocytes and neurons, and that its presence disturbed the release of neurotransmitters among neural synapses, leading to mitochondrial injury and neurocyte apoptosis. 16 Several studies have suggested that unconjugated bilirubin was neurotoxic to astrocytes and neurons, and that its presence disturbed the release of neurotransmitters among neural synapses, leading to mitochondrial injury and neurocyte apoptosis.…”
mentioning
confidence: 99%
“…15 High levels of serum NSE were noticed with cerebral venous infarction, intracranial hemorrhage, and seizure, which is positively associated with the severity of CVD in human. 16 Several studies have suggested that unconjugated bilirubin was neurotoxic to astrocytes and neurons, and that its presence disturbed the release of neurotransmitters among neural synapses, leading to mitochondrial injury and neurocyte apoptosis. 17 Although abnormally enhanced NSE and unconjugated bilirubin have been considered to be associated with the occurrence of atherosclerosis and CVD, the detailed relationship between NSE and bilirubin, and the pathogenesis and prognosis of LAAtype strokes have remained unclear.…”
mentioning
confidence: 99%
“…Dynamic changes of the NSE serum levels in acute ischemic stroke are predictive for its hemorrhagic transformation and BBB disruption [78]. An association has also been found between the NSE serum levels and severity of cerebral venous thrombosis and NSE is regarded as a predictor of clinical outcome in this process [166]. Evaluation of the NSE levels has been recommended as a valuable indicator of poor outcome or death in the course of hypoxic-ischemic brain lesion after cardiac arrest [79,167].…”
Section: Neuron-specific Enolasementioning
confidence: 99%